FORECASTING IRAQ’S CONSUMPTION OF ELECTRICITY USING TEN POLYNOMIALS (World Economics and Finance Bulletin, 2026)
The problem of this paper is to Forecasting electricity consumption in Iraq using ten Polynomials to the year 2030. The reason for this is that forecasting electricity consumption in Iraq is relatively rare and only exists at the level of specific regions or governorates, not at the national level. If it exists, it is for past years, and it is also just suggestions or for a specific year from those concerned and commenting on it only. This is in addition to the use of limits up to the third degree only in previous studies in general. To solve this problem, ten polynomial models are built with degrees from first to tenth. Computing the model’s parameters is based on the actual consumption in the period from 1993 to 2022 and applying the method of least-squares with the aid of Excel and php software. A comparison between the ten models is performed based on two measures; the root mean Square Residuals (RMSE), the complement of coefficient of determination (1-R 2 ) .The best model is the second-degree polynomial. This model is tested for sensitivity and significance and it passes the tests. The model is used for forecasting the consumptions for the period from 2023 to 2030. The forecasted consumption is 205.74 TWh in the year 2030